Digital criminology: crime and justice in digital society - Powell, Anastasia (Routledge, 2018)
Introduction: criminology and the digital society -- At the crossroad: cyber, critical and cultural criminologies -- A global context: networks, corporations and states -- Crime in real time: immediacy, immersion, and engagement -- Liminal images: criminality, victimisation and voyeurism -- Networked hate: racism, misogyny and violence -- Informal justice: digilantism, victim participation and recognition -- More than a hashtag: crime and social justice activism -- Conclusion: crime and justice in digital society